Countering Cyberattacks on the Energy Sector in the Russian Federation and the USA - V. Shestak; A. Tsyplakova (BRICS Law Journal, 2023)
The USA leads the way in the Global Cybersecurity Index, in particular 1st place in 2015, 2020 and 2nd in 2017, 2018. Researchers are interested in examining their prevention of cyberattacks as one of the main cybersecurity threats, since Russia takes only 5th place since 2020. Provided the authors underline neglecting the principle of organized response to crime, the paper examines the pros and cons of countering cyberattacks in the U.S. energy sector and compares it with the Russian Federation. The researchers have found the American strategy is based on standardization and various platforms on the grounds of so-called security in depth, while Russian approach is wider, but demands for more details and miscellaneous mechanisms to share experience. Comparing the cybersecurity plans and strategies for U.S. energy facilities, the authors note that the U.S. specialists neglect physical safety in comparison to Russia. The diversity of bodies with vague powers is a con of the American system that the Russian Federation is trying to avoid, but the interaction between government and private representatives is stronger in the United States of America.